2002
DOI: 10.1152/ajpregu.00207.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin release in normal and narcoleptic dogs after food and sleep deprivation, eating, and movement

Abstract: release in normal and narcoleptic dogs after food and sleep deprivation, eating, and movement. Am

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 58 publications
(59 reference statements)
6
70
1
2
Order By: Relevance
“…Direct injection of orexin into the brain has been shown to increase alertness and muscle tone (Hagan et al, 1999;Bourgin et al, 2000;Piper et al, 2000). In addition several reports have demonstrated the correspondence between orexin-A release and the sleep-wake cycles of rodents, monkeys and humans (Edgar et Wu et al, 2002;Zeitzer et al, 2003;Lee et al, 2005). Orexin containing neurons are inactive in sleep and maximally active in waking states characterized by exploratory activity (Lee et al, 2005;Mileykovskiy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct injection of orexin into the brain has been shown to increase alertness and muscle tone (Hagan et al, 1999;Bourgin et al, 2000;Piper et al, 2000). In addition several reports have demonstrated the correspondence between orexin-A release and the sleep-wake cycles of rodents, monkeys and humans (Edgar et Wu et al, 2002;Zeitzer et al, 2003;Lee et al, 2005). Orexin containing neurons are inactive in sleep and maximally active in waking states characterized by exploratory activity (Lee et al, 2005;Mileykovskiy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for orexin-A are located on neurons in many different brain regions making it possible for this peptide, once released, to activate a large number of areas affected by sleep and sleep deprivation (Hagan et al, 1999;Bourgin et al, 2000;Kilduff and Peyron, 2000;Piper et al, 2000;Gerashchenko et al, 2001;Yoshida et al, 2001;Wu et al, 2002;Peever et al, 2003;Lee et al, 2005;Mileykovskiy et al, 2005;Vittoz and Berridge 2006), It has recently been shown that manipulation of this system via administration of a orexin antagonist can increase sleep in rats, dogs and humans (Brisbare-Roch et al, 2007). The loss of orexin cells has been shown to cause human and animal narcolepsy (Chemelli et al, 1999;Lin et al, 1999;Nishino et al, 2000;Peyron et al, 2000;Thannickal et al, 2000;Gerashchenko et al, 2001;Wu et al, 2002;Mieda et al, 2004). Orexin-A has been shown to produce arousal, increased attention, increased muscle tone and to counteract the effects of narcolepsy (Hagan et al, 1999;John et al, 2000;Siegel, 2004;Mileykovskiy et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hypocretin has been shown to excite neurons in areas involved in the control of motoneuron activity such as the ventral tegmentum, locus coeruleus noradrenergic neurons, cholinergic and non-cholinergic neurons in the dorsolateral pontine tegmentum, and neurons in the nucleus pontis oralis (Hagan et al, 1999;Horvath et al, 1999;Ivanov and Aston-Jones, 2000;Nakamura et al, 2000;Burlet et al, 2002;Soffin et al, 2002;Xi et al, 2002). In addition, data recently provided by Kiyashchenco et al (2002) and Wu et al (2002) indicate that an increased release of Hcrt occurs during periods of wakefulness accompanied by movement. Furthermore, Torterolo et al (2003) found that Hcrt-containing neurons are activated only during behaviors that entail somatomotor activity [i.e., active wakefulness as well as carbachol-induced rapid eye movement (REM) sleep with its ancillary motor activity such as REMs and muscular twitches], whereas these neurons are not activated during wakefulness in the absence of movement or during quiet (non-REM) sleep.…”
Section: Considerations Of the Physiological Significance Of Hcrt Actmentioning
confidence: 99%
“…The hypocretinergic system has been suggested to play a role in a variety of physiological processes, most of which involve activation of the somatomotor system (Pu et al, 1998;Chemelli et al, 1999;Haynes et al, 1999;Lin et al, 1999;Siegel, 1999;Tamura et al, 1999;Kilduff and Peyron, 2000;Sutcliffe and de Lecea, 2000;Lin et al, 2002;Wu et al, 2002). Hcrtcontaining neurons project to regions that are involved in the generation of somatomotor activity Zhang et al, 2002) that provides a foundation for the concept that Hcrt is involved in the control of motor processes.…”
Section: Considerations Of the Physiological Significance Of Hcrt Actmentioning
confidence: 99%
“…This has been shown in several studies in order to evaluate the role of physical activity in OXA secretion of non-human subjects (9,13). In addition, some studies reported no change in OXA levels after physical activity in animal specimens (13,14).…”
Section: Introductionmentioning
confidence: 94%